COMBINING INNOVATIVE HISTORY LEARNING TECHNOLOGY - Ricky Aditya; Andi Zaenudin; Fatihmuhammad (Satmata: Journal of Historical Education Studies, 2024)
This study aims to examine the impact of using information and communication technology (ICT) in history education on students' motivation, understanding, and engagement. A mixed methods approach, combining quantitative and qualitative data collection, was employed to gather comprehensive insights. Based on the survey results from 100 history education students, 78% reported increased motivation, and 65% indicated enhanced understanding of historical materials after using e-learning platforms. Interviews with 10 history teachers revealed that e-learning facilitates the delivery of complex content and boosts student participation in class discussions. Additionally, e-learning provides high flexibility for students to learn anytime and anywhere, addressing the limitations of traditional classroom settings. The findings suggest that integrating ICT into history education enriches the learning experience, improves academic outcomes, and makes history education more engaging and relevant in the digital era.